INCLUSION OF THE GIANT MEALWORM (ZOPHOBAS MORIO) AS AN ALTERNATIVE PROTEIN SOURCE IN DIETS FOR P. VANNAMEI SHRIMP (BOONE, 1931) - da Silva, Vanuza de Paula do Nascimento; Lima, Fernanda Reis; Costa, Léa Carolina de Oliveira; da Costa, Saymon Rodrigues Matos; Andrade, Jackson Oliveira; Costa, Danilo Acatauassu da Silva; Brandão, Lian Valente (Seven Editora, 2025)
This study investigates the inclusion of giant mealworms (Zophobas morio) as an alternative protein source in diets for the shrimp Penaeus vannamei (Boone, 1931). The main objective is to evaluate the effects of this inclusion on the growth performance of the shrimp. The methodology involved the formulation of experimental diets with different levels of Zophobas morio inclusion and the performance of feeding trials under controlled conditions. The results indicated that the inclusion of giant mealworms can completely replace fishmeal without compromising shrimp performance, in addition to presenting additional benefits in terms of health and environmental sustainability. It is concluded that Zophobas morio is a viable and promising alternative for formulating shrimp diets, contributing to the diversification of protein sources in aquaculture. DOI: https://doi.org/10.56238/sevened2025.036-106